Sistema tutor para la aplicación de la programación mediante análisis de inteligencias - Machín-Torres, Ivelisse Teresa (Revista Científica, 2017)
The present article is part of a research for the development of an intelligent tutor system for the application of programming in the José Martí University of Sancti -Spíritus. The objective of the implementation of this system is to enhance the management knowledge related to programming issues and improve the orientation in solving problems in the university. In order to carry out the implementation of the intelligent tutoring system, the intelligent tutor systems currently in the programming area described the tools and technologies used in the developed solution (methodology, patterns, softwares, programming languages, etc.). It allowed an efficient implementation in a short time of the proposed system. The foregoing is reflected positively in a better student satisfaction and therefore in a higher performance in the teaching-learning process of the university.